The pending energy reform: distributed energy - Gamio, Pedro (2021)
Energy is an essential input to meet the various basic needs, which is why it’s fundamental for a country’s development. Furthermore, within this area, the use of renewable energies has been on the rise as their developments continues to progress. In that way, it is now possible to resort to renewable energies in distributed manner to boost the energy sector.  In this article, the author focuses on analyzing the problems faced by distributed generation in Peru. In this way, he analyzes the key actors, delves into the regulatory framework in place and addresses the existing barriers for the implementation of distributed energy. Finally, he proposes a matrix of solutions to drive towards a decentralized, distributed and accessible for all Peruvians.